Articulated Homogeneity in Cumulative Sentences. (20th December 2021) - Chatain, Keny
Abstract: In this work, I use cumulative readings of every (Champollion, 2010, 2016a ; Haslinger & Schmitt, 2018 ; Kratzer, 2003 ; Schein, 1993 ) as a tool to investigate homogeneity in cumulative readings in general. Based on a new observation about the homogeneity properties of cumulative readings of every, I argue that the homogeneity properties of cumulative readings arise from the interaction of multiple operators, each operator contributing one exhaustive participation inference which disappears in negative contexts. I identify these operators with the thematic role heads in a Neo-Davidsonian semantics. The resulting theory is able to predict the homogeneity properties of cumulative sentences from the homogeneity properties of their arguments and the position of these arguments.